Investigating chinese language learners’ reading comprehension for different meaning types - Mi, Soon Kim; Hyun, Jung Kim (Penerbit UKM, 2014)
The Chinese government has published an official guide specifying the aims for reading in Chinese and the expected comprehension levels for different proficiency learners, with regard to teaching and learning Chinese as a second or foreign language. However, due to lack of teacher training for its implementation, this guide has rarely been used for teaching reading to Chinese language learners and has rarely been used for evaluating their reading ability. Therefore, it appears that teaching and assessing reading comprehension have not been based on a theoretical background of reading ability. The purpose of this study is twofold: (1) to provide validity evidence of a Chinese reading test developed based on a theoretical model of reading ability; and (2) to examine reading test performance of Chinese learners with various reading ability levels. For the purpose of this study, reading ability was defined based on a meaning-based model that included three layers of reading comprehension: literal, intended, and implied meanings of a reading text. A total of 248 Korean university students were divided into three levels, and their test performances were analyzed and compared for the three meaning types using structural equation modeling and regression analysis. The results suggest that the test performance structure represented the meaning-based model in general, thereby providing validity evidence of the test. Further analyses revealed that the three groups differed from one another with respect to their understanding of literal, intended, and implied meanings. The findings provide pedagogical implications for teaching Chinese language learners with different reading proficiency levels.